Hubungan Tingkat Pengetahuan Keluarga dengan Upaya Pencegahan Penularan Tuberculosis Paru di Wilayah Kerja UPT Puskesmas Pahandut: The Relationship of Family Knowledge with the Prevention of Tuberculosis Transmission Lungs in the Working Area of the Health Center Pahandut - Sugion Sugion; Fitriani Ningsih; Riska Ovany (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
One way of transmitting pulmonary Tuberculosis is through droplets of phlegm (droplet nuclei) when a patient coughs or sneezes, especially to those closest to the patient, namely the family who lives in the same house as the patient. Family behavior in prevention plays an important role in reducing the risk of pulmonary TB transmission, such as using eating or drinking utensils simultaneously, lack of lighting in the house, and patients still spitting carelessly. The purpose of this study was to determine the relationship between the level of family knowledge and the prevention of transmission of pulmonary tuberculosis in the work area of the Pahandut Health Center. The design of this study used analytical research methods using a cross-sectional design. The population in this study were all patients with pulmonary Tuberculosis, with a total sample of 58 respondents. The sampling method used is purposive sampling. The research data was taken using a questionnaire. After tabulating the existing data, it was analyzed using the Chi-Square analysis test. The results showed a relationship between the family knowledge level and efforts to prevent transmission of pulmonary tuberculosis in the Pahandut Health Center Work Area (with a P value of 0.000 < 0.05). Puskesmas can improve and maintain the quality of services or programs that have been provided to families and pulmonary Tuberculosis patients and provide counseling about prevention related to pulmonary Tuberculosis.